‘Anâshir al-Jumal baina al-Lughataini al-‘Arabiyyah wa at-Tâmiliyyah (Dirâsâh Taqâbuliyyah) - Muhammadu Sainulabdeen Zunoomy; Mohammed Cassim Sithy Shathifa (Jurnal Internasional Pendidikan Bahasa Arab, 2022)
Each language has a specific pattern in sentence structure. Based on this, sentence pattern in Arabic language differs from Tamil language since they are from two different linguistic families namely Semitic language family and Dravidian language family respectively. Therefore, this research focuses on studying sentence pattern in Arabic and Tamil languages by exposing similarities and dissimilarities between them. This research uses contrastive descriptive methodology. This research finds that there are more dissimilarities than similarities in sentence pattern between Arabic and Tamil languages whence use of gender, number, tense, adjective, genitive and articles. As for the similarities, they are in sentence elements, nominal sentence and interrogative sentence.